Evaluating the influence of gradient applied voltages on electro-enhanced sequence batch reactor treating aniline wastewater: System performance, microbial community and functional genes. (20th February 2023) - He, Jing; Zhang, Qian; Li, Meng; Ming, Tingzhen; Feng, Jiapeng; Peng, Haojin; Su, Junhao; Zhang, Yunjie
Abstract: Aniline is an important industrial raw material. Its complex structure makes it difficult to be chemically oxidized and its intense biological toxicity also increases the difficulty of biodegradation. Therefore, electro-biological system based on biological processing have become a new direction in the field of environmental governance. Comparative evaluation of the performance differences of reactors at gradient external voltages (1.5, 3.0, 4.5 and 6.0 V) was investigated to seek the optimal applied voltage in the electro-enhanced sequence batch reactor treating aniline wastewater. Results showed that all reactors degraded aniline effectively, the aniline degradation rate of five reactors was about 100%. However, the highest removal efficiency of total nitrogen was obtained at 1.5 V, up to 88.89%. Compared with control, high applied voltage (>3.0 V) deteriorated the nitrification performance and the removal efficiency of TN was descended along with the increase of applied voltages. Besides, proper applied voltage promoted the secretion of extracellular polymeric substance. The sludge activity such as specific oxygen utilization rate (SOUR), dehydrogenase (DHA) was highly increased under the applied voltage of 1.5V, so did the Ammonia monooxygenase (AMO) and nitrate reductase (NAR). Based on the high-throughput sequencing analysis, introducing applied voltages altered the microbial diversity and community structure. Particularly, several functional genera such as autotrophic nitrifying bacteria and denitrifying bacteria were enriched in the system at 1.5V. Network analysis also found that the cooperative/competitive relationship between key functional genus became simpler under the higher voltage. Additionally, the contribution of the functional flora to key metabolic pathways (benzoate and nitrogen metabolism) and the expression of various functional genes was augmented at the 1.5V applied voltage. Graphical abstract: Image 1 Highlights: The voltage at 1.5V showed highest removal efficiencies of aniline and nitrogen. High applied voltage (>3.0 V) deteriorated the nitrification performance in ESBR. Applying voltage shifted the microbial diversity and community structure. The metabolic function and the expression of functional genes were enhanced at 1.5V.